Analysis of Oil Palm Replanting Implementation Behavior In Tawang Rejo, Seluma - Wahyu Utami; Yossie Yumiati; Eko Sumartono (UNIVED Press, Dehasen University Bengkulu, 2025)
Purpose: This study aims to analyse the factors influencing smallholder farmers’ behaviour in oil palm replanting, including demographic factors, attitudes, object characteristics, situational factors, replanting systems, and government policies in Tawang Rejo Village, Seluma Regency. Methodology: A quantitative approach was employed using a survey of 123 oil palm farmers who had undertaken replanting activities. Data were collected through structured interviews and field observations and analysed using Structural Equation Modelling–Partial Least Squares (SEM-PLS) with SmartPLS version 4.0. Results: Demographic factors have a positive and significant effect on farmers’ perceptions (T = 5.484; P = 0.000) and on their intention to undertake replanting (T = 2.499; P = 0.012). Farmers’ attitudes also exert a significant influence on perception. Object characteristics significantly affect the intention to undertake replanting (T = 2.638; P = 0.008) and farmers’ behaviour through intention (T = 2.406; P = 0.016); however, they do not have a significant effect on perception (P > 0.05). Furthermore, perception has a positive and significant indirect effect on farmers’ behaviour through intention (T = 3.170; P = 0.002). Findings: Farmers’ perceptions and intentions function as significant mediating variables linking external factors to actual replanting behaviour among smallholder oil palm farmers. Novelty :The novelty of this study lies in the integration of the Theory of Planned Behaviour (TPB) with context-specific variables related to smallholder oil palm replanting, as well as the application of sequential mediation analysis involving perception and intention. Originality: This study combines a behavioural approach (TPB) with the specific context of smallholder oil palm replanting programmes, which have previously been analysed predominantly from economic and policy perspectives, thereby offering a relatively new behavioural insight. Conclusion: Smallholder farmers’ replanting behaviour is primarily influenced by demographic factors, attitudes, and object characteristics. Type of Paper: Research article.